Developing barcode scan system of a small-scaled reverse vending machine to sorting waste of beverage containers - Erikson Ferry Sinaga; Richard Irawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Reduce, Reuse, and Recycle is a campaign which aims to reduce the production of waste. Industry used plastic bottle and cans to store the beverage. A research was done by University of Georgia, United States and was published by Wall Street Journal stated that Indonesia is the second predicate country which produced and mismanaged plastic waste in the world. This condition shoud be overcome and this research project was intended to develop reverse vending machine (RVM) to sorting waste of beverage containers either plastic bottles or cans as a campaign to reduce the production of waste. This RVM machine uses barcode scanning as the sorting system to determine whether the plastic bottle or can could be recycled or not. In order to check the weight of the beverage container, a load cell sensor is used to check whether the beverage container is empty or not. The machine will receive the container from the conveyor station, check the weight, and finally transfer it to the sorting station. The container will be sorted as cans or plastic bottle by the aid of barcode scanning and compare it to database. Furthermore, the plastic bottle will be sorted as clear or colored plastic bottle. Unrecyclable plastic or can container or any unemptied container will be classified as rejected container and be returned to the user through the outlet passage. The performance testing was done with 12 different types of plastic bottle and can and 10 samples for each type, so there were total 120 items tested and the result showed that the success rate was 94% while the processing time was varying in between 8 to 13 seconds.